Studi Literatur: Dampak Media Digital Terhadap Kebudayaan di Indonesia - Aryanto, Tiara Nisa; Tjahjadi, Elvira; Pureklolon, Thomas Tokan (Da'watuna: Journal of Communication and Islamic Broadcasting, 2026)
The development of digital media has transformed the ways in which Indonesian society represents and interprets culture. This literature study analyzes how digital media shapes cultural representation through the processes of encoding and decoding within the framework of Stuart Hall’s Representation Theory. The findings indicate that cultural content displayed on digital platforms is predominantly presented in short and aesthetic visual forms, leading to simplification of meaning and shifts in cultural context. Digital media also triggers changes in cultural identity and authority, where content creators and algorithms play significant roles in shaping public cultural interpretation. These findings show that while digital media expands cultural visibility, it simultaneously contributes to the shallow understanding of culture when not accompanied by contextual representation. This study highlights the importance of digital cultural literacy to ensure the sustainability of cultural meaning in the digital era.